Penataan Linieritas Guru Sekolah Dasar: Analisis Kebijakan pada Keputusan Menteri Pendidikan, Kebudayaan, Riset, dan Teknologi Nomor 56 Tahun 2022 - Hidayati, Ummi; Isnaeni , Diyan; Hidayati, Rahmatul (Jurnal Ilmiah Penegakan Hukum, 2023)
The concept of teacher linearity in Kepmendikbudristek Number 56 of 2022 still refers to Permendikbud Number 46 of 2016 article 4. In Kepmendikbudristek Number 56 of 2022, teacher workload in education units implementing the Independent Curriculum refers to the provisions of laws and regulations governing teacher workload fulfillment, principals, and school superintendents. The concept of teacher linearity in the independent curriculum is even broader in its interpretation. Fulfilling the teacher's teaching load of at least 24 hours per week is not only by carrying out learning but can also be carried out by mentoring in intra-curricular, co-curricular, and extra-curricular activities or by becoming a project coordinator for strengthening the profile of Pancasila students. The legal consequence of the linearity arrangement for Elementary School teachers in Kepmendikbudristek Number 56 of 2022 that teachers who fulfill the provisions get the rights as stipulated in Article 14 paragraph (1) of Law Number 14 of 2005 concerning Teachers and Lecturers. Non-linear teachers cannot claim their rights. To obtain rights according to the provisions, teachers should take part in educational programs by higher education institutions and teacher professional development organized by the government.